Peningkatan Kompetensi Guru melalui Pelatihan Learning Management System SMK Putra Pelita Tenjolaya - Wardani, Hadidtyo Wisnu; Utama, Gunawan Pria; Prasetyo, Basuki Hari Prasetyo; Pramusinto, Wahyu; Saputro, Ari (Ikatan Ahli Informatika Indonesia, 2024)
abstrack